2019
DOI: 10.3906/vet-1901-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant activity of bee products of different bee races in Turkey

Abstract: Bee products with high bioactive properties have a very important place in human nutrition. Biochemical properties of these products such as honey, pollen, and propolis vary according to flora, season, bee race, and production methods. In this study, the biological activities of honey, bee pollen, and propolis samples from four bee races in Turkey (Apis mellifera caucasica, Apis mellifera anatoliaca, Apis mellifera syriaca, and Apis mellifera carnica) were examined. Besides the determining of total polyphenol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
(47 reference statements)
3
13
0
Order By: Relevance
“…Total polyphenolic content is an important parameter in the determination of the phenolic content in natural products and high phenolic content indicates high biological activity (Kolayli et al, 2016;Can et al, 2015;Kaygusuz et al, 2016). Another study reported that bee breeds affected the quality of propolis and other bee products (Saral et al, 2019). The present study findings demonstrated that the total phenolic content was at the highest level in pre-season, gradually decreased over time and reached the lowest level in the post-season.…”
Section: Phenolic Contents and Profilessupporting
confidence: 60%
“…Total polyphenolic content is an important parameter in the determination of the phenolic content in natural products and high phenolic content indicates high biological activity (Kolayli et al, 2016;Can et al, 2015;Kaygusuz et al, 2016). Another study reported that bee breeds affected the quality of propolis and other bee products (Saral et al, 2019). The present study findings demonstrated that the total phenolic content was at the highest level in pre-season, gradually decreased over time and reached the lowest level in the post-season.…”
Section: Phenolic Contents and Profilessupporting
confidence: 60%
“…The findings show that propolis is a good source of phenolic substances. The literature states that propolis samples from different geographical origins have a good antioxidant antimicrobial, antifungal and antiviral (Avian influenza virus) activity (Pietta 2000 ; Pratsinis et al 2010 ; Yildiz et al 2014 ; Saral et al 2016 , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant capacity was reported as 46.1±13.0 µmol Trolox E/g bee bread [22]. It is stated that total phenolic content of pollen samples varies between 0.41-7.38 mg GAE/g and antioxidant capacity varies between 8.69-75.65 µmol FeSO 4 .7H 2 O/g [23].…”
Section: Resultsmentioning
confidence: 99%